Collaborative freshwater planning: changing roles for science and scientists. Issue 1 (2nd January 2018) - Berkett, Natasha; Fenemor, Andrew; Newton, Mark; Sinner, Jim
ABSTRACT: Collaborative approaches to freshwater planning are increasingly popular. In principle, collaborative processes allow wider access to all forms of knowledge, referencing the socio-ecological system and stakeholder values. Relevant science must be more broadly defined. Here we explore how the roles and skillsets of scientists and the nature of science knowledge differ in collaborative freshwater planning compared to traditional consultative processes, to assist those designing and participating in such processes. Our observations are drawn from interviews with scientists, policy planners, facilitators and an indigenous adviser from project teams managing collaborative processes in four regions of New Zealand. Results indicate that the role of the scientist in a collaborative process is less top-down informer, and more facilitator of learning. Thus 'front-room' scientists involved in collaborative planning processes require a broader skill set than those required for a traditional consultative process. Humility and an ability to see other participants' points of view are traits facilitating successful engagement with indigenous groups and stakeholders. More science  is needed on social, economic and cultural values. Risk and uncertainty can be tested using scenarios. Employing a wider range of science disciplines and scientists who act as integrators enables a greater sharing of local and indigenous knowledge even though such knowledge cannot always be tested or modelled.